2018
DOI: 10.12795/revistafuentes.2018.v20.i1.04
|View full text |Cite
|
Sign up to set email alerts
|

¿Cómo valoran los estudiantes de magisterio la docencia que reciben?

Abstract: The objective of this work is to present the assessments that the teaching students do about the teaching they receive. The data were obtained from a sample of 61 students belonging to three groups of an optional subject of the mention of Special Education of the Master's degree in Primary Education that is taught in the first semester of the fourth year that attended this subject in the course 2016-2017. In order to do this, a teacher review survey was made up of 5 open-ended questions (AUTOR, in press) that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
(2 reference statements)
2
3
0
Order By: Relevance
“…Our findings also indicated that students considered that these kinds of methods required greater effort from teachers and students, considering active methods to increase the complexity of activities, as stated in other studies [29,33]. However, we emphasize that previous studies already contemplated the fact that these methods encourage the creation of a succession of learning challenges, but, once they overcome them, they stimulate proactive actions and a critical attitude towards learning [34,35].…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…Our findings also indicated that students considered that these kinds of methods required greater effort from teachers and students, considering active methods to increase the complexity of activities, as stated in other studies [29,33]. However, we emphasize that previous studies already contemplated the fact that these methods encourage the creation of a succession of learning challenges, but, once they overcome them, they stimulate proactive actions and a critical attitude towards learning [34,35].…”
Section: Discussionsupporting
confidence: 76%
“…Furthermore, our findings showed that the methods used in the classroom were compatible with the use of ICTs, coinciding with the objectives of the university framed within the EHEA [30][31][32]. According to the previous literature [33][34][35][36][37], university students show a positive perception towards the use of active methods and the introduction of ICTs in the classroom as well as towards the management and organization of office hours, considering them motivating and that they stimulate participation in the classroom.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations